Glyphosate and its formulations Roundup Bioflow and RangerPro alter bacterial and fungal community composition in the rat caecum microbiome - Mesnage, Robin; Panzacchi, Simona; Bourne, Emma; Mein, Charles A.; Perry, Melissa J.; Hu, Jianzhong; Chen, Jia; Mandrioli, Daniele; Belpoggi, Fiorella; Antoniou, Michael N. (Frontiers in Microbiology, 2022)
The potential health consequences of glyphosate-induced gut microbiome alterations have become a matter of intense debate. As part of a multifaceted study investigating toxicity, carcinogenicity and multigenerational effects of glyphosate and its commercial herbicide formulations, we assessed changes in bacterial and fungal populations in the caecum microbiota of rats exposed prenatally until adulthood (13 weeks after weaning) to three doses of glyphosate (0.5, 5, 50 mg/kg body weight/day), or to the formulated herbicide products Roundup Bioflow and RangerPro at the same glyphosate-equivalent doses. Caecum bacterial microbiota were evaluated by 16S rRNA sequencing whilst the fungal population was determined by ITS2 amplicon sequencing. Results showed that both fungal and bacterial diversity were affected by the Roundup formulations in a dose-dependent manner, whilst glyphosate alone significantly altered only bacterial diversity. At taxa level, a reduction in Bacteroidota abundance, marked by alterations in the levels of Alloprevotella, Prevotella and Prevotellaceae UCG-003, was concomitant to increased levels of Firmicutes (e.g., Romboutsia, Dubosiella, Eubacterium brachy group or Christensenellaceae) and Actinobacteria (e.g., Enterorhabdus, Adlercreutzia, or Asaccharobacter). Treponema and Mycoplasma also had their levels reduced by the pesticide treatments. Analysis of fungal composition indicated that the abundance of the rat gut commensal Ascomycota Kazachstania was reduced while the abundance of Gibberella, Penicillium, Claviceps, Cornuvesica, Candida, Trichoderma and Sarocladium were increased by exposure to the Roundup formulations, but not to glyphosate. Altogether, our data suggest that glyphosate and its Roundup RangerPro and Bioflow caused profound changes in caecum microbiome composition by affecting the fitness of major commensals, which in turn reduced competition and allowed opportunistic fungi to grow in the gut, in particular in animals exposed to the herbicide formulations. This further indicates that changes in gut microbiome composition might influence the long-term toxicity, carcinogenicity and multigenerational effects of glyphosate-based herbicides.